Ant fauna (Hymenoptera: Formicidae) of Quetta, Balochistan, Pakistan - Ali Ahmed, Hina; Noor, Sabina; Sani, Imran Ali; Kanwal, Safoora; Khudaidad, Shereen; Khawar, Masooma (Pusat Sistematik Serangga ,UKM, 2013)

(untitled)
The ant fauna of Quetta, Northern Pakistan was studied using hand collected samples. A total of 1865 individuals were sampled comprising of seven species belonging to three subfamilies. A preliminary checklist of the ant species collected from Quetta city is presented. The most common subfamily observed was Myrmicinae with an abundance value of 66.8% and the most frequent species encountered was the Myrmicine Pharoah Ant, Monomorium pharaonis (60%). The least common species encountered were Solenopsis invicta (Fire ant) and Tetramorium sessile (Pavement ant), also belonging to the subfamilyMyrmicinae with an abundance value of 3.2% and 3%, respectively. The subfamilies Formicinae (3 species) and Dolichoderinae (1 species) were found to be moderately common with abundance values of 18% and 15%, respectively.